Implementation Strategy of Forest Tree Seed in South Kalimantan Province - Dede J. Sudrajat; Kurniawati P. Putri; Rizky Ary Fambayun (Jurnal Perbenihan Tanaman Hutan, 2020)
The green revolution movement is an action to change people's behavior quickly and precisely to care for environment quality through planting activities in South Kalimantan Province. This movement requires the quality forest tree seed supply, thus requiring research to determine an integrated and systematic strategy for developing forest tree seed programs in South Kalimantan in the next 10 years. SWOT analysis (strengths, weaknesses, opportunities, threats) with the analytical hierarchy process approach is used to determine the planning strategy. The results of the analysis show that the position of forest tree seed implementation programs is in an investment position, which shows a big opportunity but still has internal constraints/weaknesses. Weakness-opportunities strategies were chosen with 6 programs, i.e.: increasing the human resources competence; construction of facilities and infrastructure for seeds and seedlings certification; organizing certification of seed sources, seedling quality and seed quality; development of superior seed sources; strengthening of quality seed and seed production systems; and the provision of technological information, documentation and supervision systems of the seed and seedling distribution. This strategy can be described in a work program which is expected to be able to improve the performance of the forest tree seed implementation in order to provide quality seeds and seedlings and to become a community economic generator from the forest tree seed sector in South Kalimantan.